Mental health problems in refugee and immigrant primary school children in Flanders, Belgium. (October 2022) - Kevers, Ruth; Spaas, Caroline; Colpin, Hilde; Van Den Noortgate, Wim; de Smet, Sofie; Derluyn, Ilse; De Haene, Lucia
Background: European countries face the challenge of promoting refugee and immigrant children's well-being within their host communities, invoking the necessity of adequate mental health assessment. This study aims to contribute to document the psychosocial well-being of primary school refugee and non-refugee immigrant children in Flanders, Belgium. Method: A total of 120 children (8–12 years old) with migration backgrounds participated in the study. Through self-report, parent and teacher questionnaires we scrutinized externalizing and internalizing behavioral problems, post-traumatic stress problems, and classroom relationships. Results: Thirty percent of the participants reported high levels of post-traumatic stress; around 25% reported a high or very high prevalence of internalizing and externalizing behavioral problems. Self-reported mental health problems are elevated in comparison to the general population. Refugee children did not report more difficulties than their immigrant peers. In the perception of parents and teachers, respectively 20% and 5% of children showed high or very high amounts of internalizing and externalizing behavioral difficulties. Almost 70% of the participants perceived the class climate as unsafe. Conclusions: Refugee and immigrant children are at risk for mental health difficulties, and experience classroom dynamics as markedly distressful. School-based intervention might be particularly suited to support these children's psychosocial well-being in resettlement.